Exercise in cancer - Rajarajeswaran, P; Vishnupriya, R (Indian Journal of Medical and Paediatric Oncology, 2009)
Physical exercise has attracted increased interest in rehabilitation of oncological patients. The purpose of this paper is to review the literature and summarize the evidence of physical exercise in preventing cancer, its ability in attenuating the effect of cancer and its treatments and to provide guidelines for exercise prescription Review of recent literature by electronic search of MEDline (Pub Med), Cancer lit, Cochrane libraries, CINAHL were done using Keywords and the variables were identified and systematically evaluated. There is strong evidence for reduced risk of colorectal and breast cancer with possible association for prostate, endometrial and lung cancer with increasing physical activity. Exercise helps cancer survivors cope with and recover from treatment; exercise may improve the health of long term cancer survivors and extend survival. Physical exercise will benefit throughout the spectrum of cancer. However, an understanding of the amount, type and intensity of exercise needed has not been fully elucidated. There is sufficient evidence to promote exercise in cancer survivors following careful assessment and tailoring on exercise prescription.
Keywords: Exercise; cancer; prevention; rehabilitation